Manipulating the extracellular matrix: an animal model of the bladder pain syndrome. Issue 1 (21st October 2016) - Offiah, Ifeoma; Didangelos, Athanasios; O'Reilly, Barry A.; McMahon, Stephen B.
Abstract : We demonstrate a novel animal model of bladder pain syndrome which specifically reproduces the pathological and clinical aspects of disease seen in the human condition. Abstract: Bladder pain syndrome (BPS) is associated with breakdown of the protective uroepithelial barrier of the urinary bladder allowing urinary constituents access to bladder sensory neurons. Although there are several animal models of cystitis, none specifically relates to BPS. Here, we aimed to create such a model using enzymatic digestion of the barrier proteoglycans (PGs) in the rat. Twenty female Wistar rats were anaesthetized and transurethrally catheterized. Ten animals were treated with 0.25IU of intravesical chondroitinase ABC and heparanase III to digest chondroitin sulphate and heparin sulphate PGs, respectively. Ten animals received saline. Following PG deglycosylation, bladders showed irregular loss of the apical uroplakin and a significant increase in neutrophils, not evident in the control group. Spinal cord sections were also collected for c-fos analysis. A large and significant increase in fos immunoreactivity in the L6/S1 segments in the treatment vs control bladders was observed. Cystometry was performed on 5 treatment and 5 control animals. Analysis revealed a significant increase in micturition reflex excitability postdeglycosylation. On a further group of 10 animals, von Frey mechanical withdrawal thresholds were tested on abdominal skin before and after PG digestions. There was a significant decrease in abdominal mechanical withdrawal threshold postdeglycosylation compared with controls. The results of this animal study suggest that many of the clinical features of BPS are seen after PG digestion from the bladder lumen. This model can be used to further understand mechanisms of pain in patients with BPS and to test new therapeutic strategies.